Talent identification in sepak tak.raw: From a coach's perspective - Maail, Che Hazrj Che (Universiti Sains Malaysia, 2016)
The main objective of this study is to qualitatively explore the talent identification criteria of sepak takraw players from a coach's perspectives, while the specific objectives are to identify physical, psychological and skill of the game criteria of selecting the ideal sepak takraw players from a coach perspective. Seven male (n=7) developmental level coaches participated in the current study (age : between 40-53 years old ; coaching experience ; 10-24 years). All the coaches were currently appointed by MSSK as a part time coach. A face to face semi-structured questions interview was carried out to obtain in depth-information from the coaches. All interview lasted between 30-60 minutes. The finding summarized that there were three main themes that emerged from the interview on how coaches identify potential players ; ( 1) skill of the game, (2) physical and (3) mental and emotional skill of the players. Skill of the game were classified into two sub-themes (i.e. basic skills and specific skills), meanwhile physical was categorised based on position (i.e. height of the players) and finally emotional and mental skills were divided into two subthemes that consisting of outside competition (i.e. passion) and during competition (i.e. mental toughness and focus). Basic skills referred to simplest (fundamental) skills that should be mastered by all the players in any position (i.e. types of kick, heading and knee kick) while specific skills involved the skills required based on position such as tekong (i.e. type of serve, ability to make target and height of leg elevated), killer (i.e. type of spike, ability to make target, height of jumping and ball blocking) and feeder (i.e. best ball juggler, ball setting and ball receiving). The physical component involved height of the players, length of the legs and flexibility. The sub-theme for physical component was based on position such as tekong (i.e. tall, long legs and high flexibility), killer (i.e. tall and long legs) and feeder (i.e. short). Finally, the mental and emotional skills were identified by the coaches based on outside and during competition by assessing the commitment given by the players towards sepak takraw, face expression and ability to execute skills. Finding from the study concluded that most of the coaches emphasised the important of game skills ability compared to physical and mental and emotional skills. However, physical and psychological skills were also important to help the players perform to their best.